Fluid and electrolyte disturbances in heat illness - Noakes, T. D. (International Journal of Sports Medicine, 1998)
Three exercise-related heat illnesses are described in the literature -- heat cramps, heat exhaustion or heat syncope, and heat stroke. Of these, only exercise-induced heat stroke, which occurs infrequently, is definitely a heat illness caused by an increased rate of heat production unmatched by adequate heat loss causing progressive heat retention with the body temperature rising to dangerously high levels (> 41 degrees C). The terms heat cramps and heat exhaustion are misleading as neither is caused by an elevated body temperature; nor is there evidence that either is caused by specific fluid or electrolyte abnormalities. Cramps occur during or after exercise regardless of whether the exercise is performed in the heat or the cold, or in water. Current evidence suggests that a spinal neural mechanism may induce cramping that is unrelated to biochemical changes in either blood or in the affected skeletal muscles. Historically, heat exhaustion has been described as a condition of postural hypotension that develops immediately on termination of exercise especially when performed in the heat by unacclimatised persons. No modern evidence conflicts with this historical interpretation. Nor have more modern studies shown that exercise-related heat exhaustion is necessarily caused by specific fluid or electrolyte abnormalities. Similarly, there is no published evidence that fluid and electrolyte abnormalities are critical determinants of exercise-related heat stroke. This does not negate firm evidence that dehydration has important physiological effects that impair heat loss and exercise performance especially in the heat. Rather, it shows that exercise-induced heat stroke requires powerful initiating factors, in addition to dehydration which occurs commonly during prolonged exercise, whereas heat stroke is an extremely rare event. The purpose of this review is to provide an alternate, more critical review of the conditions that are considered to be exercise-related heat disorders and to evaluate the aetiological role of fluid and electrolyte disturbances. There is a need to better understand these conditions so that their clinical management can be based on modern information rather than on dated ideas, many of which have survived unchallenged for more than 50 years.